Nova ocorrência de †Mawsoniidae (Sarcopterygii, Actinistia) na Formação Morro do Chaves, Cretáceo Inferior da bacia de Sergipe-Alagoas, nordeste do Brasil - Gallo, Valéria; Carvalho, Marise Sardenberg Salgado de; Santos, Hugo Ricardo Secioso (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2010)
The goal of this paper is to describe a new occurrence of †Mawsoniidae in the Morro do Chaves Formation, Sergipe-Alagoas Basin. This stratigraphical unit is represented by an intercalation of coquina and shale beds, deposited in a lacustrine paleoenvironment during the Upper Barremian (Lower Jiquiá local stage). The description is accomplished on the basis of new and more complete material, represented by articulated bones of the palatoquadrate and lower jaw, as well as by gular plate. It was assigned to the genus Mawsonia based on the presence of a stout angular conspicuously ornamented with wrinkles and ridges, as well as palatoquadrate with a single strengthening ridge on its lateral surface. When this new occurrence of Mawsonia was compared with the other genera of Mawsoniidae occurring in Brazil (i.e., Axelrodichthys and Parnaibaia), it was verified that it differs clearly from Axelrodichthys by the inclination of the suspensorium (obliquely oriented in Mawsonia versus vertically oriented in Axelrodichthys). Regarding Parnaibaia, the ornamentation of the angular and gular plate is more delicate in this genus.